2017
DOI: 10.1007/s12020-017-1261-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interaction of DGAT2 and FAAH in the development of human obesity

Abstract: We detected two rare variants in DGAT2 with no significant difference between obese and lean individuals. One novel heterozygous nonsense variant c.382C > T (p.R128*) was identified in one obese subject but not in 219 lean subjects and another 1190 lean subjects. Notably, in vitro study showed that R128* mutation severely damaged the TG-biosynthesis ability of DGAT2, and all other R128* carriers in the pedigree were lean. Thus, we further identified a loss-of-function variant c. 944G > T (p.R315I) in FAAH in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Similar decreases were found in mice treated with AAV‐shDGAT2 or a DGAT2 inhibitor . A low HDL‐C level (~25 mg/dL) was also reported in a proband with nonsense mutation in DGAT2 , and an exome‐wide association study showed that humans who are heterozygous for a nonsense mutation in DGAT2 have lower HDL‐C levels . Our data show that a low HDL‐C phenotype is reproduced in a murine model where DGAT2 is deficient only in hepatocytes.…”
Section: Discussionsupporting
confidence: 83%
“…Similar decreases were found in mice treated with AAV‐shDGAT2 or a DGAT2 inhibitor . A low HDL‐C level (~25 mg/dL) was also reported in a proband with nonsense mutation in DGAT2 , and an exome‐wide association study showed that humans who are heterozygous for a nonsense mutation in DGAT2 have lower HDL‐C levels . Our data show that a low HDL‐C phenotype is reproduced in a murine model where DGAT2 is deficient only in hepatocytes.…”
Section: Discussionsupporting
confidence: 83%
“…In mice, ACSL5 (Acyl-CoA synthetases 5) regulated systemic energy metabolism such that the knockout of this gene can prevent the onset of obesity and insulin resistance [50]. DGAT2 (Diacylgycerol acyltransferase 2) is an essential catalyst of triglyceride biosynthesis, which is important given that excessive triglyceride accumulation within adipose tissues is a key facet of obesity [51]. Overexpression of FAAH (Fatty acid amide hydrolase) can suppress DGAT2 expression and triglyceride synthesis, and these genes may interact with one another to in uence adiposity [51].…”
Section: Discussionmentioning
confidence: 99%
“…DGAT2 (Diacylgycerol acyltransferase 2) is an essential catalyst of triglyceride biosynthesis, which is important given that excessive triglyceride accumulation within adipose tissues is a key facet of obesity [51]. Overexpression of FAAH (Fatty acid amide hydrolase) can suppress DGAT2 expression and triglyceride synthesis, and these genes may interact with one another to in uence adiposity [51]. ACSS2 (Acetyl-CoA synthetase short-chain family member 2) codes for a cytosolic enzyme that catalyzes acetate activation for use in the context of lipid synthesis and energy production.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphism-trait association studies cannot determine whether VLDLR is responsible for variation in a trait or whether a closely linked locus influences the trait. Many studies have revealed that obesity candidate genes were associated with genetics, nutritional disease, gastrointestinal and developmental disorders, and cancer (Castro et al, 2017;Ning et al, 2017). Peroxisome proliferator-activated receptor alpha (PPARα) and retinoid X receptor alpha (RXRα) were identified as central nodes, also called hub molecules (Kunej et al, 2013).…”
Section: Discussionmentioning
confidence: 99%